Focus Time: Effectiveness of Computer Assisted Protected Time for Wellbeing and Work Engagement of Information Workers - Saha, Koustuv; Iqbal, Shamsi (Annual Symposium on Human-Computer Interaction for Work 2023 (CHIWORK 2023), 2023)
Having little time for focused work is a major challenge of information work. While research has explored computing-assisted user-facing solutions for protecting time for focused work, there is limited empirical evidence about the long-term effectiveness of these features on wellbeing and work engagement. Towards this problem, we study the effects of automatically scheduling time for focused work on people’s work calendars using the Focus Time feature on Outlook calendars. We conduct an experimental study over six weeks with 15 Treatment and 10 Control participants who responded to survey questions on wellbeing and work engagement throughout the study. We find that the Treatment participants showed significantly higher wellbeing, including increased excitement, relaxation, and satisfaction, and decreased anger, frustration, tiredness, and stress. We study the needs, benefits, and challenges of scheduling focus time, and discuss the importance of enabling mechanisms for focused work in organizations and design recommendations for tools supporting focused work.